Complications in the parenteral nutrition - Erhan, Ömer Lütfi; Akın, Mustafa (Fırat University, 2001)
The patients are at the greatest risk for metabolic complications during the first few weeks of nutritional therapy. Complications related to parenteral nutritional therapy are typically catheter-related, related to metabolic homeostasis or related to changes in the gastrointestinal tractus function. Because the nutrient is delivered directly into a central vein, complications related to the catheter and metabolic homeostasis may be potentially life-threatening. Clinicians who are trained to recognize these complications and initiate appropriate therapy before co-morbid conditions develop.

Nütrisyonel tedavinin ilk birkaç haftasında metabolik komplikasyon açısından hastalar büyük risk altındadırlar. Parenteral nütrisyonla ilişkili olanları; keteterle, metabolik homeostazla ve gastrointestinal traktüs fonksiyonundaki değişikliklerle ilişkili olarak sayabiliriz. Nütrient doğrudan santral ven içine verildiğinden kateterle ilişkili komplikasyonlarla hemeostazla ilişkili olanlar yaşamı tehdit edici olabilirler. Deneyimli klinisyenler bu komplikasyonları çok iyi tanıyabilir ve daha morbit koşulların gelişimine fırsat verdirmeden uygun tedaviye başlayabilirler.
PARENTERAL NÜTRİSYONDA KOMPLİKASYONLAR